The effects of sex offender stereotypes on potential juror beliefs about conviction, victim blame and perceptions of offender mental stability - Borhart, Hannah M. (Applied psychology in criminal justice, 2015)
The current study sought to investigate the widely held myth that sex offenders are sociallyisolated with few or no friends and no romantic partners. Vignettes describing a sex offensewere presented to the participants in which the level of social support reported was varied(no friends vs. friends vs. fiancee). In addition, whether the offender was previously known to the victim (acquaintance vs. stranger) was varied. Results indicated that participants'beliefs about guilt differed among the defendant's reported level of social support andprevious knowledge of the victim. Namely, when the sex offender was described as the moststereotypical sex offender (i.e., a loner assaulting a stranger), participants were less sure of their belief that he should be convicted compared to all other conditions. Additionally,reported level of social support and priorknowledge of the victim influenced participants'judgments of the defendant and the victim. These judgments showed that the participants believed the most stereotypical sex offender (i.e., loner who assaulted a stranger) was most mentally unstable, and the judgments of victim blame increased as the described offender became increasingly disparate from the stereotypical sex offender. Implications within thecourtroom and for future research are discussed.